INCLUSION OF CHILDREN WITH DISABILITIES IN THE REGULAR EDUCATION SYSTEM: ACHIEVEMENTS, ADVANCES AND CHALLENGES - Silva, Elizabeth Ferreira da; Silva, Marcela Gomes da; Carvalho, Márcia Cristina Silva de; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
The inclusive education guaranteed by law, right to welcome all the children regardless of your physical conditions emotional, social, intellectualsl inguistics among others. This work aims to objective show a little education with children in special needs, approaching lrarning difficulties fundamentals epistemological to effect school inclusion. It can be concluded that it is necessary to provide teachers with training to cover knowledge about the different disabillities and the education needs related to them, to provide the building of physical space and material resources, in addition to specific assistance.